Social Analysis of Policy Implementation Regional Head Election Voter Registration in North Sulawesi Province - Zulkifli Golonggom; Heru Nurasa; Entang Adhy Muhtar; Caroline Paskarina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study analyzes the social implementation of voter registration policy in the regional head elections in North Sulawesi Province in 2017. According to the eligible residents in the constituency, the process of voter registration through voter list update to produce a voter list is completely fulfilled voting rights. Thus, during the vote, those who have the right to vote can exercise their voting rights. But in the course of the trip, the administrative activities of the preparation of voter lists by the Voter Data Update Officer (PPDP) conducted Matching, and Research (Coklit) encountered obstacles, voter data collection in each village clashed with the constraints of population indifference to be registered as voters and the obligation of recording electronic ID cards, the socio-economic condition of the community that the majority as farmers prioritize their time and needs with agricultural activities and on the other hand the migration of population because of duties and jobs and work and education outside the electoral district.